Physiological and interspecific factors determine diel changes in phytoplankton bio‐optical properties - Nicholas Baetge; Kimberly H. Halsey; Jason R. Graff; Brian Ver Wey; Toby K. Westberry; Amanda E. Appel; Guillaume Bourdin; Charlotte Begouen Demeaux; Emmanuel Boss; Michael J. Behrenfeld (Limnology and Oceanography, 2024)
Bio‐optical properties of marine phytoplankton retrieved through satellite remote sensing are used to estimate ocean productivity and carbon cycling. Daily activity of phytoplankton is attuned to the predictable light fluctuations of the diel cycle. Field and laboratory studies have documented diel changes in phytoplankton growth, division, and respiration, carbon and pigment content, cell size, photosynthetic efficiency and rate, and DNA replication and transcription. Many of these physiological changes can alter cellular optical properties and contribute to diel variations in bulk absorption and scattering properties. Consequently, understanding phytoplankton contributions to diel optical cycles is essential for improving algorithms that convert remote sensing data to biological rates and stocks. Here, we describe time‐resolved cellular, photophysiological, and bio‐optical properties for three cultured phytoplankton ranging in cell size from ~ 1 to 6 μ m: Ostreococcus lucimarinus , Synechococcus (WH8102), and Thalassiosira pseudonana , all of which can significantly contribute to phytoplankton abundance and/or biomass in the open and coastal ocean. This work is the first to characterize complete diel cycles in absorption and attenuation for O. lucimarinus and backscattering for all these species. Results show that the percent increase from the minimum to maximum values over the diel cycle ranged between ~ 24–121%, ~ 31–235%, and ~ 25–198% for particulate absorption, attenuation, and backscattering, respectively. Diel changes in bio‐optical properties also differed in both timing and magnitude across phytoplankton species, demonstrating the importance of contextualizing remote sensing observations with phytoplankton community composition.